Visualizing and inferring chromosome segregation in the pedigree of an improved banana cultivar (Gold Finger) with genome ancestry mosaic painting - Cenci, Alberto; Martin, Guillaume; Breton, Catherine; D’Hont, Angélique; Yahiaoui, Nabila; Sardos, Julie; Rouard, Mathieu (MDPI, 2023)
Banana breeding faces numerous challenges, such as sterility and low seed viability. Enhancing our understanding of banana genetics, notably through next-generation sequencing, can help mitigate these challenges. The genotyping datasets currently available from genebanks were used to decipher cultivated bananas’ genetic makeup of natural cultivars using genome ancestry mosaic painting. This article presents the application of this method to breeding materials by analyzing the chromosome segregation at the origin of ‘Gold Finger’ (FHIA-01), a successful improved tetraploid variety that was developed in the 1980s. First, the method enabled us to clarify the variety’s intricate genetic composition from ancestral wild species. Second, it enabled us to infer the parental gametes responsible for the formation of this hybrid. It thus revealed 16 recombinations in the haploid male gamete and 10 in the unreduced triploid female gamete. Finally, we could deduce the meiotic mechanism lying behind the transmission of unreduced gametes (i.e., FDR). While we show that the method is a powerful tool for the visualization and inference of gametic contribution in hybrids, we also discuss its advantages and limitations to advance our comprehension of banana genetics in a breeding context.